Education And Training On Searching For Teaching Materials From The Internet For Teachers In Pangkep District - Edy Sabara; Retyana Wahrini; Mustamin (ENGAGEMENT: Jurnal Pengabdian Masyarakat, 2023)
This Community Service Program (PkM) is entitled Education and Training on Searching Teaching Materials from the Internet for Teachers in Pangkep Regency. In the midst of globalization, teachers should not be like frogs in a shell. Teachers must have broad and globalized insights as an effort to improve education. Teachers should not only transfer information/learning materials that are "stale" (not contemporary) to students. The material taught by teachers does not solely come from textbooks, but there is information as learning material that can be obtained through other sources. One source that can be used as a medium to browse the latest information is the internet. The internet is currently not a rare item. Almost every time we use the internet in every activity to find various references and information needed. Currently in Pangkep district, teachers certainly have a variety of learning media and teaching materials used in the teaching and learning process, teachers access a variety of information for their teaching materials. It's just that to be able to access it, you need skills in the form of ways or techniques to make the internet a medium for searching learning resources. In fact, most teachers in Pangkep District do not know and master the techniques of operating and using the internet. Given the importance of this, it is necessary to hold training on the use of the internet as a medium for searching learning resources for teachers in Pangkep District.